Short-wavelength automated perimetry in patients with migraine - ŞAHİN, ÖZLEM (SPRINGER, 2006)
The aim was to investigate short-wavelength sensitivity deficits in patients with migraine. Fifteen migraine and 18 age-matched healthy volunteers with normal ophthalmologic examination participated in this study. Migraine characteristics were graded by the Migraine Disability Assessment Questionnaire (MIDAS). All participants underwent SWAP (short wavelength amplitude perimetry) testing using a Humphrey field analyzer; there was a 30-2 presentation pattern. Short wavelength amplitude perimetry parameters for mean deviation (MD; p < 0.0001) and pattern standard deviation (PSD; p < 0.0001) were significantly worse in the migraine group. In the migraine group 53.3%. of eyes had glaucoma hemi-field tests (GHT) outside normal limits and 10 of these had early glaucomatous visual field loss. Statistically significant correlations were found between frequency of migraine attacks and MD (p=0.02; r=0.56) and PSD (p=0.03; r=0.41) and also between the MIDAS score and MD (p=0.03; r=0.49) and PSD (p=0.04; r=0.51). In all migraine cases with early glaucomatous visual field defect a corresponding site of the head was predominantly involved in headache (p=0.03). Some patients with severe migraine have earlier defects on SWAP suggesting a common vascular insult of glaucoma and migraine, and all migraine cases with high MIDAS scores should be further evaluated for early glaucomatous visual field defects using SWAP.
Keywords: SWAP; migraine; glaucoma; LOW-TENSION GLAUCOMA; VISUAL-FIELD LOSS; OPEN-ANGLE GLAUCOMA; WHITE-ON-WHITE; SENSITIVITY; HEADACHE; DEFICITS; YELLOW; SAMPLE; SCORE